Numerical Analysis of Impulse Turbine for Isolated Pilot OWC System. (2nd September 2013) - Liu, Zhen; Jin, Jiyuan; Cui, Ying; Fan, Haiwen
Abstract : Oscillating water column (OWC) is the most widely used wave energy converting technology in the world. The impulse turbine is recently been employed as the radial turbine in OWC facilities to convert bidirectional mechanical air power into electricity power. 3D numerical model for the impulse turbine is established in this paper to investigate its operating performance of the designed impulse turbine for the pilot OWC system which is under the construction on Jeju Island, Republic of Korea. The proper mesh style, turbulence model, and numerical solutions are employed to study the velocity and air pressure distribution especially around the rotor blade. The operating coefficients obtained from the numerical simulation are compared with corresponding experimental data, which demonstrates that the 3D numerical model proposed here can be applied to the research of impulse turbines for OWC system. Effects of tip clearances on flow field distribution characteristics and operating performances are also studied.